2010
DOI: 10.1029/2009jb006643
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Subduction Zone Curvature and its Dependence on the Trench Velocity and the Slab to Upper Mantle Viscosity Ratio

Abstract: [1] Three-dimensional laboratory models of upper mantle subduction are presented investigating the effect of the trench velocity (v t ) and the slab to upper mantle viscosity ratio (h SP /h UM ) on trench curvature and slab curvature. One set of experiments varies h SP /h UM from 66 to 1375. Another set of experiments modifies v t through applying different velocities at the trailing plate. The results show that the radius of trench curvature (R TC ) progressively decreases with continuous trench retreat due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 80 publications
(161 reference statements)
14
32
0
Order By: Relevance
“…The olivine fabrics in the anhydrous aseismic PHS slab may change to D-type because of high stress induced by slab bending, for which seismic anisotropy is V x  > V y  > V z . In a number of subduction zones on Earth, the slab geometry generally shows an increasing dip angle at a greater depth in the mantle, possibly affected by trench retreat and slab rollback 47 . Thus, the above-mentioned x and z axes for the olivine fabric in the slab rotated counterclockwise and replaced each other with unchanged y axis, and V x is the velocity in the vertical direction while V z and V y are the velocities in the horizontal plane.…”
Section: Discussionmentioning
confidence: 99%
“…The olivine fabrics in the anhydrous aseismic PHS slab may change to D-type because of high stress induced by slab bending, for which seismic anisotropy is V x  > V y  > V z . In a number of subduction zones on Earth, the slab geometry generally shows an increasing dip angle at a greater depth in the mantle, possibly affected by trench retreat and slab rollback 47 . Thus, the above-mentioned x and z axes for the olivine fabric in the slab rotated counterclockwise and replaced each other with unchanged y axis, and V x is the velocity in the vertical direction while V z and V y are the velocities in the horizontal plane.…”
Section: Discussionmentioning
confidence: 99%
“…The toroidal flow of the mantle around the eastern Alaska slab edge and steepening of the slab dip predicted by the 3D models of the Alaska subduction‐transform system are suggestive of slab rollback [ Garfunkel et al , 1986; Kincaid and Griffiths , 2003; Schellart , 2004; Funiciello et al , 2006; Stegman et al , 2006] and thereby retreat of the trench in eastern Alaska. 3D laboratory experiments of free subduction indicate that during trench retreat, the trench geometry evolves into an arcuate shape with the concave side directed away from subducting plate [ Schellart , 2004; Funiciello et al , 2006; Schellart , 2010a]. Along the greater than 3000 km length of the Aleutian‐Alaska subduction zone, the sense of curvature of the plate boundary changes concavity [ Page et al , 1989; Gudmundsson and Sambridge , 1998; Ratchkovski and Hansen , 2002; Bird , 2003].…”
Section: Discussionmentioning
confidence: 99%
“…The general subduction evolution of the models is similar to previous laboratory and numerical models of progressive subduction in three‐dimensional space that use a similar (low) slab to upper mantle effective viscosity ratio ( η SP / η UM ≈ 10 2 ). Earlier narrow‐slab models also showed rapid trench retreat and a trench curvature that is concave toward the mantle wedge [e.g., Stegman et al , 2006; Morra et al , 2006; Schellart , 2004, 2010; Schellart et al , 2007], and wide‐slab models also showed slow trench migration and an overall convex trench geometry with concave edges [ Schellart et al , 2007; OzBench et al , 2008; Stegman et al , 2010b]. …”
Section: Discussionmentioning
confidence: 99%